Энергоэффективная система панорамного ультразвукового обнаружения препятствий для слепых - Костенко, Виталий Леонидович; Кондратьев, Сергей Борисович; Ядрова, Марина Васильевна; Попов, Дмитрий Александрович (НТУ "ХПИ", 2018)
Разработана энергоэффективная система ультразвукового обнаружения препятствий для слепых. Показана возможность повышения эффективности системы – расширения угла обзора, снижения энергопотребления, повышения времени автономной работы от элемента питания без подзарядки, за счет использования современной элементной базы, выбора оптимальной тактовой частоты и алгоритма работы микроконтроллера. Приведены результаты разработки программной модели и кода программы работы микроконтроллера. На основе данных исследований был собран и испытан макет устройства. Наличие трех ультразвуковых датчиков позволяет расширить угол обзора и определять наличие препятствий прямо перед человеком, а также слева и справа от него.

The analysis of ultrasonic obstacle detection devices for the blind was carried out. An energy efficient detection system has been developed. The possibility of increasing the efficiency of the system is shown - the expansion of the viewing angle, the reduction of power consumption, the increase in the battery life from the battery without recharging due to the use of a modern element base, the selection of the optimal clock frequency and the microcontroller operation algorithm. The results of the development of the program model and the program code of the microcontroller program in the C language are presented. The program is based on two main fragments that provide the definition of obstacles and distances to them. Programmatically creates a sequential survey of sensors and the possibility of moving the inactive sensor into silence mode, which allows to realize the energy saving mode of the device and reducing power consumption, while its battery life without recharging the battery is increased 4–5 times compared to analogues.
Energy efficient system of panoramic ultrasonic obstruction obstacles for the blind
Keywords: ультразвуковой датчик; микроконтроллер; звуковой излучатель; программные коды; энергопотребление; ultrasonic distance sensor; microcontroller; sound emitter; program codes